Metabolism of Shah Alam, Klang and Petaling Jaya: insights from material flow analysis/ Muhammad Fadhil Mohd Aris ... [et al.] - Mohd Aris, Muhammad Fadhil; Karuppannan, Subramaniam; Masngut, Mohd Izwan; Md Rashid, Razi Ikhwan; Ishak, Ahmad Razali; Shafie, Farah Ayuni (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Urbanization is a process of growth for both economic and social activities. Unplanned urbanization lead to negative impacts especially to the environment and human beings living in the city. The aim of this study is to provide an insights on the environmental impacts of Shah Alam, Klang and Petaling Jaya. Materials Flow Analysis (MFA) approach was used to assess the input resources of residential area: electricity usage, water consumption, food consumption and output resources: ambient air quality, wastewater production and solid waste generation. The input-output data were obtained from government agencies and utility providers. The primary data collection was done through a reliability tested questionnaire to the city residents. Any national data obtained were then downscaled to a regional scale. Through the study, the result showed there are significant difference for the water and food expenses between the three cities. Meanwhile, there is no significant different for the electricity use between the cities. Klang has contribute the most in terms of output resource of gases, wastewater and solid waste outcome compared to Shah Alam and Petaling Jaya due to the city's numbers of population. In general, 0.188 kg/cap/day of energy will contribute to about 0.455 kg/cap/day of carbon dioxide emission, 95.3% out of 236.1 kg/cap/day of water usage will become the wastewater and about 0.38 kg/cap/day of food consumption will generate about 4.5 kg/cap/day of solid waste.